Does the Greening of Supply Chain Have Any Impact on Sustainability and Organizational Performance of Firms in Thai Chemical Industry? - Chandej Charoenwiriyakul; Nopadol Burananuth; Sittichai Reungjarungpong; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2019)
The prime objective of the current study is to investigate the determinant of the green supply chain, the impact of the green supply chain on the sustainable performance and lastly the impact of the sustainable performance eon the organizational performance of the Thai chemical firms. The study has employed the survey-based method to answer the research questions as manufacturing managers are surveyed as ultimately, manufacturing managers are responsible for the performance of the organizations for which they work. The SEM-PLS is used to analyze the data collected from the manufacturing managers of Thai chemical firms. The literature provides considerable empirical evidence regarding the linkage of supply chain success with the ERP information mechanism, which helps to share information between the partnering firms. The findings of the study have provided support to the hypotheses results. The consideration of four green constructs in the model explains that cooperation causes largest influence on the environmental performance, next comes the investment recovery and eco-design. However, no significant association was found between cooperation with customers and economic or environmental performance particularly in case of greater customer pressure for adopting environment friendly practices in Thailand.